A fictional commons : Natsume Sōseki and the properties of modern literature - Bourdaghs, Michael K. (Duke University Press, 2021)
"Michael K. Bourdaghs presents a radical reframing of the works of Natsume Sōseki--widely considered to be Japan's greatest modern novelist--as critical and creative responses to the emergence of new forms of property ownership in nineteenth-century Japan."--